2013
DOI: 10.1177/1756283x13502838
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D level is an independent predictor of poor outcomes in Clostridium difficile-associated diarrhea

Abstract: Background: The incidence, recurrence, and all-cause mortality rate for Clostridium difficileassociated diarrhea (CDAD) has increased markedly over the past 10 years despite treatment. Low vitamin D levels are known to impair immune responses to infection and are associated with increased mortality. We compared the role of patient comorbidity measured by the Charlson Comorbidity Index (CCI) with vitamin D levels to ascertain whether vitamin D levels were an independent variable affecting the outcome of CDAD or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
2
21
1
2
Order By: Relevance
“…Wang et al . similarly demonstrated that individuals with CDI who were deficient in vitamin D were less likely to resolve infection 36 , consistent with data from van der Wilden et al . who demonstrated an inverse correlation between severity of CDI and plasma vitamin D levels 35 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Wang et al . similarly demonstrated that individuals with CDI who were deficient in vitamin D were less likely to resolve infection 36 , consistent with data from van der Wilden et al . who demonstrated an inverse correlation between severity of CDI and plasma vitamin D levels 35 .…”
Section: Discussionsupporting
confidence: 86%
“…A few recent studies have examined this association between vitamin D levels and CDI in non-IBD cohorts 3336 . In a study from the Veterans affairs population, Youssef et al .…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this finding may be differences in the duration of follow‐up time used by the researchers. For instance, when CDI recurrence was defined as “within 30 days,” Arramraju et al 12 and Wang et al 13 found a significant association between lower 25(OH)D status and recurrence; however, when CDI recurrence was evaluated in a longer follow‐up period of 56 and 90 days, Abdelfatah et al 5 and Wong et al 16 did not find an association. We must point out, however, that study considerations may have had a role in this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was shown that patients >70 years of age given vitamin D supplementation consumed less antibiotics (50% reduction) compared to the placebo group . Hypovitaminosis D (<50 nmol L −1 ) has been reported to be an independent predictor of nonresolution of clostridium difficile‐associated diarrhoea . Individuals with chronic pulmonary disease are reported to have significantly more exacerbations in the presence of hypovitaminosis D .…”
Section: Discussionmentioning
confidence: 99%